1987
DOI: 10.2118/13749-pa
|View full text |Cite
|
Sign up to set email alerts
|

Forty-Seven Years' Gas Injection in a Preferentially Oil-Wet, Low-Dip Reservoir

Abstract: Summary. Crestal gas injection has been used since 1938 for pressure maintenance in a preferentially oil-wet reservoir in the Bahrain field. This paper updates the gas injection history through July 1984, presents the benefits of gas injection, and discusses the finding that recovery in the gas-contacted area was greater than in water-invaded blocks. Introduction This is an update of two previous papers by Cotter and Shehabi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Furthermore, the fault throws and the areas of communication between Ab and the underlying zones controlled the degree of communication and the type of fluids being introduced into the Ab zones. Earlier studies has shown that Aab zone is continuously receiving fluid and pressure support in certain areas from the underlying higher pressure Mauddud zone (which is undergoing gas injection 8,9 ) through an intermediate sandstone layer, the Wara sandstone which exist in the form of erratic sand lenses distributed irregularly all over the field 6,7 .…”
Section: Production Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fault throws and the areas of communication between Ab and the underlying zones controlled the degree of communication and the type of fluids being introduced into the Ab zones. Earlier studies has shown that Aab zone is continuously receiving fluid and pressure support in certain areas from the underlying higher pressure Mauddud zone (which is undergoing gas injection 8,9 ) through an intermediate sandstone layer, the Wara sandstone which exist in the form of erratic sand lenses distributed irregularly all over the field 6,7 .…”
Section: Production Data Analysismentioning
confidence: 99%
“…The source of water in this reservoir is lower reservoirs. And, the connectivity with lower reservoirs is provided by both fracture corridors and a high-porosity-permeability "Ac sand reservoir beneath Ahmadi 8,9 . Oil and gas production data indicated that wells in north and south have performed much better than the crestal wells.…”
Section: Production Data Analysismentioning
confidence: 99%
“…This zone has been on gas injection since 1938. 5 The gas injection is very effective in most parts of the reservoir, except the northern and southern flanks, where the water drive dominates. Laboratory studies and cased-hole logs, 6,7 show that large quantity of residual oil (S or of nearly 50 %) will be left in such a system either by gas flooding or by water flooding (Figure: 8).…”
Section: Oil Wet Systemmentioning
confidence: 99%
“…6 is obtained from Equation (9). The continuity equation (17) providesthe requiredrelation between RA(z, 7) and thedrainage rate fromeachelement,…”
Section: -Fluid Flow Problemmentioning
confidence: 99%